'Hard' is 'soft': exploring the dangers of the 'hard'/'soft' distinction. (4th June 2007) - McCabe, Darren
This paper argues that the hard/soft distinction used in relation to new management interventions is potentially dangerous because it serves to reproduce the status quo by reinforcing taken-for-granted assumptions about the world. Thus considering innovations to be 'hard' can result in a failure to think through the social implications of one's actions. It is suggested that our understanding of organisations can be enhanced through reflecting on the dichotomy and its underlying assumptions. It is thought that through such reflection, the number of innovations that are instigated with little thought for employees and their Quality of Working Life can be reduced, even though asymmetrical power relations are likely to remain. These issues are explored by drawing on some qualitative research from a company that introduced Statistical Process Control (SPC), which has been described as a 'hard' intervention, in conjunction with Total Quality Management (TQM).